Epidemiology study of leprosy patients in the district of Bombana Southeast Sulawesi Province, Indonesia - Tosepu, Ramadhan; Effendy, Devi Savitri; Imran, La Ode Ali; Asfian, Pitrah (International Journal of Research in Medical Sciences, 2017)
Background: Leprosy remains a public health problem in Bombana. In 2011 cases of leprosy were recorded for 34 cases or 2.4 per 10.000 population. In January 2012, the number of patients with infectious diseases is increased to 53 cases. Methods: The method used is a survey method with cross sectional approach, with a total sample of 34 people. The epidemiological characteristics of respondents surveyed consisted of the characteristics (gender, knowledge, and personal hygiene), the characteristics of the place (population density), and the characteristic time diagnosed (months). Results: The results showed that the characteristics of lepers many male sex (55.9%), elementary education (58.8%), had less knowledge about the disease (76.5%), did not work (52.9%), personal hygiene enough (85.3%), residential density has not qualified (88.2%) and most likely to be diagnosed in the period January to March (41.2%). Conclusion: The incidence of leprosy in Bombana is still very high and therefore required a treatment in patients on a regular basis and it takes effort to prevent the spread of the disease that can be restricted.